Direct Numerical Simulation of Laminar-Turbulent Transition on Grids with Local Refinement - D.I. Okhotnikov (Учёные записки Казанского университета: Серия Физико-математические науки)
This paper considers a method of building composite grids with local refinement for direct numerical simulation of flows in a channel with transverse cylindrical rib at moderate Reynolds numbers. The specific characteristic of the flows is LTT (laminar-turbulent transition) in a trace behind the rib. Grids characterized by resolution of the whole spectrum of vortices are needed for numerical simulation of LTT, thereby leading to significant computational costs and a need for supercomputers. The purpose of the study is to generate a cost-efficient computational grid based on the above-described method, as well as to test this grid for flows in a channel with the following two types of ribs: a semicircular ridge on the lower wall of the channel and cylinder near it. The grid has been built using the HybMesh generator, which is based on the composite approach, when the grid is built from a set of structured subdomains, in which grid generation and refinement is defined by several control parameters. As a result of superposition of the grids built in subdomains, a composite grid from structured parts superposed with unstructured inserts has been obtained. The results of the direct numerical simulation on a grid for the problem with a semicircular ridge have turned out to be in a good agreement with the results of the laboratory experiment, both along the profiles of average velocity and the profiles of pulsations. The results obtained on the grid for the problem with a circular cylinder have demonstrated good agreement with the results of the numerical simulation on high-definition grids, predicting in the right way the transition point to three-dimensionality in a trace behind the cylinder. The method of building composite grids with the use of the HybMesh generator allows to generate cost-efficient composite grids taking into account all flow peculiarities and allowing for calculations using medium-powered computers.